BRS Catiana: irrigated rice cultivar with high yield potential and wide adaptation - Rangel,Paulo Hideo Nakano (2019)
Abstract BRS Catiana is an irrigated rice cultivar with a medium cycle and excellent grain quality, suited for cultivation in 17 Brazilian states. It has a high yield potential (15,535 kg ha-1) and a mean yield of 7,253 kg ha-1, wide adaptation and late senescence (stay green trait).